PEMBUATAN ASAP CAIR DARI TEMPURUNG KELAPA,TONGKOL JAGUNG, DAN BAMBU MENGGUNAKAN PROSES SLOW PYROLYSIS - Reta, Karolus Boromeus; Iskandar, Taufik (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Pyrolysis process is the thermal decomposition of biomass in the absence of oxygen. Pyrolysis process coconut plantation to be able to transform waste materials that have a sale value, with good conversion. Results of the pyrolysis process in the form of bio-charcoal, tar and liquid smoke grade 3. Liquid smoke consists of grade 3, grade 2, and grade 1 , the classification is based on the amount of liquid smoke berbahanya compounds in liquid smoke, thereby affecting the function of the liquid smoke. 3 grade liquid smoke is smoke liquid pyrolysis results that have not undergone a process of purification . Liquid smoke grade 3 is not used as a food preservative , but is used in rubber processing , deodorizing , and wood preservatives to resist termites . Grade 2 liquid smoke to food preservatives instead of formalin with taste of smoke (smoked meat or smoked fish ) . Whereas grade 1 liquid smoke is used as food preservatives such as meatballs , noodles , tofu , spices and barbeque . Compounds responsible for the preservation process is phenol . Presence of phenol with high boiling point in a smoke is high, so antibacterial substances can prevent bacterial spoilage . Pyrolysis process begins with sample preparation yaitutempurung coconut , corn cobs and bamboo, then enumeration , drying , and weighing . Then do the pyrolysis process padatemperatur 300 oC . The results of which form the smoke cairgrade pirolis 3 in the analysis by using GC - MS in Organic Chemistry Laboratory , State University of Brawijaya generate the content of phenolic compounds , carbonyl compounds , acidic compounds , and compounds benzo (a) pirena . From the results of the analysis showed that the amount of phenolic compounds and acetic acid compounds multiply comparable to the temperature rise . Of the three samples used in this study were obtained grade 3 samples of liquid smoke coconut shell , corn cob and bamboo has better quality than the other samples , ie : at a temperature of 300 C , producing phenol compound content of the most highest with corn cobs concentration of 6.73 % at a retention time of 4,502 minutes and compounds acetic Acid is the most supreme of corn cob with a concentration of 84.45 % at a retention time of 2.240 minutes . Keywords : slow pyrolysis , liquid smoke , phenol, and acetic acid.